Studi Kelayakan Pengembangan Pelabuhan Bolok Ditinjau Berdasarkan Aspek Finansial - Joka, Umbu (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2019)
Development of Bolok ferry port in Kupang East Nusa Tenggara Province requires a financial feasibility study, the results of which are very influential on investment projects, because every investment project that will be carried out is not always in a favorable condition for investors. This research was conducted with 3 (three) stages, namely the calculation of cash out (expenditure), cash in calculation (income), calculation of selection criteria. Primary data collected include observation data of research locations, namely crossing docks and conducting interviews in the form of question and answer, while for secondary data, namely East Nusa Tenggara Central Bureau of Statistics, PT. ASDP Indonesia Ferry Persero Kupang branch, KSOP, Transportation Agency, regarding dock fee standards, NTT Province regional layout plan, and Kupang Regency profile. Forecasting the use of the volume level of the dock with a linear method to project the volume of user use in the next 20 years, then calculate the cost of the crossing dock cash in and cash out. After the prediction of the dock crossing volume level, cash in, and cash out is obtained, followed by cash flow analysis, analysis of the financial feasibility of the dock (NPV, IRR, and Payback Period). in the future, the results of the NPV value obtained is 47,636,116,308, which means NPV> 0, then the project is declared